2010
DOI: 10.1097/pcc.0b013e3181ce7427
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of pediatric intensive care: Who was admitted, what happened in intensive care, and what happened afterward*

Abstract: Over the last three decades, the length of stay in the pediatric intensive care unit and the severity of illness have not changed, but there has been a substantial reduction in pediatric intensive care unit mortality. However, the proportion of survivors with moderate or severe disability increased significantly. Some children who would have been allowed to die in 1982 and 1995 were kept alive in 2005-2006, but survived with disability. This trend has important implications for our patients and their families,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
271
3
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(302 citation statements)
references
References 32 publications
16
271
3
12
Order By: Relevance
“…Namachivayam et al 26 described the profile of children in a reference PICU in Australia in the past three decades and reported a reduction of 13% in traffic accidents in 1982 to 7% in 2005 and 2006, due to stricter laws in that country and the implementation of educational measures. This is contrary to what is observed in Brazil, where these patients crowd the PICUs, due to cranial t rauma, severe orthopaedic injuries, and politrauma.…”
Section: Resultsmentioning
confidence: 99%
“…Namachivayam et al 26 described the profile of children in a reference PICU in Australia in the past three decades and reported a reduction of 13% in traffic accidents in 1982 to 7% in 2005 and 2006, due to stricter laws in that country and the implementation of educational measures. This is contrary to what is observed in Brazil, where these patients crowd the PICUs, due to cranial t rauma, severe orthopaedic injuries, and politrauma.…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications have drawn attention to the prevalence of neurological morbidity following critical illness in pediatric patients and the importance of brain injury as a contributing cause of death in the PICU [3,4,141,142]. These studies highlight the opportunity for development and implementation of neuroprotective strategies in a wide variety of illnesses that are encountered in the PICU.…”
Section: Neuromonitoring and Neuroprotection In The Picumentioning
confidence: 99%
“…Reported experience with pediatric neurocritical care consultation services suggest that nearly one quarter of patients admitted to the PICU have, or are considered to be at risk for acute neurological injury [2]. PICU patients with neurological injury also have higher mortality, more long-term morbidity, and longer length of hospital stay [3]. A recent study found that more than half of the patients who died in a tertiary care center PICU had an acute brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates for critically children have declined dramatically [1]. The greatest gains are occurring in higher-risk groups in whom the appropriateness of critical care was previously questioned.…”
mentioning
confidence: 99%
“…The three decades of Melbourne data [1] show that over time the group with pre-existent health needs stands to benefit more than previously healthy children if one defines a ''good outcome'' as functional status equal to, or better than, prior to admission (Fig. 1).…”
mentioning
confidence: 99%